Alterations of the ocular surface epithelial mucins 1, 2, 4 and the tear functions in patients with atopic keratoconjunctivitis - Dogru, M.; Okada, N.; Asano-Kato, N.; Igarashi, A.; Fukagawa, K.; Shimazaki, J.; Tsubota, K.; Fujishima, H. (Clinical and experimental allergy, 2006)
Summary Background An increased understanding of the ocular surface alterations at the cellular level in the conjunctiva and the cornea, may help explain the pathogenesis and the subsequent clinical appearance of atopic ocular allergies, which may be potentially blinding. Purpose To investigate MUC 1, 2 and 4 alterations, tear function and the ocular surface disorder in patients with atopic keratoconjunctivitis. Methods Twenty‐eight eyes of 14 atopic keratoconjunctivitis patients as well as 22 eyes of 11 age‐and sex‐matched normal subjects were studied. The subjects underwent corneal sensitivity measurements, Schirmer's test, tear film break‐up time (BUT), fluorescein and Rose Bengal staining of the ocular surface, conjunctival impression cytology and brush cytology. Impression cytology samples underwent periodic acid‐Schiff and immunohistochemical staining with MUC 1, 2 and 4 antibodies. Brush cytology specimens underwent evaluation for inflammatory cell numbers and quantitative real‐time‐PCR for MUC 1, 2 and 4 mRNA expression. Patient eyes with fluorescein and Rose Bengal scores greater than four points were regarded to have significant epithelial disease in this study. Results The mean corneal sensitivity and BUT values were significantly lower in atopic patients with significant epithelial disease, compared with patients with insignificant epithelial disease and controls (P<0.01). Brush cytology specimens from patients with significant epithelial disease revealed significantly higher numbers of inflammatory cells (P<0.01). Specimens from patient eyes showed positive staining for MUC 1, 2 and 4. MUC 1, 2 and 4 mRNA expressions were significantly higher in eyes with significant epithelial disease compared with eyes with insignificant epithelial disease and eyes of control subjects. Conclusion Ocular surface inflammation, decline in corneal sensitivity, tear film instability, changes in conjunctival epithelial MUC 1, 2 and 4 mRNA expressions were thought to be important in the pathogenesis of atopic ocular surface disease.